Prospects of Public Land Management and Issues of Tenure Security in Southern Tarai of Nepal - Acharya, Sushant; Manandhar, Prabin; Nepali, Purna Bahadur; Sapkota, Mahendra (New Angle: Nepal Journal of Social Science and Public Policy, 2016)
Public land management (PLM), a community based common property land management approach, was initiated since 2003 in the southern Tarai of Nepal to generate agroforestry resources and support the livelihoods of local people. Contemporary researches demonstrate that PLM practice has been able to bring positive changes at local level but also warn that issues related to tenure security are challenging to sustain the current practice. In this context, this paper explores the prospects of public land and then critically examines issues related to tenure security. From an in-depth case study in the five purposively selected PLM groups of Nawalparasi and Rupandehi districts, we concluded that PLM has been instrumental in promoting the livelihood of poor, women and religious minorities including environment conservation and safeguarding the common-property land. Similarly, the tenure related issues we examined are: loose contractual arrangement among government authority and local people, imposition of land tax, issue of timber harvest permit and no overarching government authority to take judicial action. We argue that though community based PLM practices have been able to create additional assets and provide benefit to local people, tenure related issues are so critical that if we fail to respond on time, it could end up with the tragedy of ruining the agro-forestry resources established in public land.